Consumption of fish and seafood by pregnant Polish women and the supply of docosahexaenoic acid and eicosapentaenoic acid from these products - Broś-Konopielko, Magdalena; Białek, Agnieszka; Oleszczuk-Modzelewska, Luiza; Zaleśkiewicz, Barbara; Różańska-Walędziak, Anna; Teliga-Czajkowska, Justyna; Tokarz, Andrzej; Czajkowski, Krzysztof (Family Medicine & Primary Care Review, 2017)
Background. Fish and seafood are the main source of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA ) in the diet. There is no available data concerning the intake of fish and seafood by pregnant Polish women. Objectives. The purpose of the study was to analyze the consumption of fish and seafood by pregnant women and to estimate the daily supply of DHA and EPA provided by these products. Material and methods. A fish and seafood intake questionnaire was given to 204 full-term pregnant women. Results . 23% of the surveyed women did not eat any fish during pregnancy; 58% ate fish once a week or once every two weeks; 19 of pregnant women ate fish 2–3 times a week; only 5% of respondents ate seafood. The surveyed pregnant women recorded a total of 0.28 (range 0–1.9) g DHA per day and 0.131 (range 0–1.16) g EPA per day from the supply of fish in their diet. The recommended daily requirement varies depending on the source: for DHA (0.2 g/day or 0.6 g/day) and for EPA (0.22 g/day); thus, 52% or even 86% and 80% of surveyed women, respectively, obtained through their diet of fish and seafood less than the recommended daily intake of DHA and EPA . Conclusions . Fish and seafood consumption during pregnancy is either low or rare. The amount of fish and seafood in the diet of pregnant women does not meet the daily requirement for docohexaenic acid and eicosapentaenoic acid. Dietary modifications in pregnancy are strongly advised in order to prevent a deficiency of DHA and EPA .